Probing the Impact of Buffer Layer on CuGaSe2 Based Solar Cells for Photovoltaic Performance - Si Abdallah, S.; Zaidi, B.; Alali, A. Sait; Al-Dmour, H. (PLEIADES PUBLISHING LTD, 2025)
With a particular focus on addressing environmental sustainability challenges, this study investigates the impact of buffer layers on the efficiency of CuGaSe2 based solar cells using SCAPS simulation software program. The research examines how variations in absorber layer thickness, series resistance (RS), and shunt resistance (RSh) affect electrical properties such as open-circuit voltage (VOC), short-circuit current density (Jsc), and overall efficiency. Additionally, the influence of acceptor density (NA) and donor density (ND) on performance was analysed. The increasing the absorber layer thickness improves short-circuit current density (Jsc) by enhancing light absorption, which leads to more electron-hole pairs being generated. However, thicker layers also increase the distance charge carriers must travel, raising the likelihood of recombination, which reduces open-circuit voltage (Voc). Additionally, thicker layers may introduce higher series resistance and non-ideal contact effects, further lowering Voc. The optimal thickness was determined to be 0.5 mu m, resulting in efficiencies of 21.09% for CdTe cells and 28.58% for CdS cells. Transitioning from CdTe to CdS buffer layers further enhances efficiency, while higher shunt resistance and donor density, alongside lower series resistance, contribute to improved performance. These results emphasize the importance of optimized CuGaSe2-based solar cells performance parameters scuh as buffer layer thickness, acceptor defect density, donor defect density, series and shunt resistance on higher efficiency and better performance of the solar cells. The study provides a direction for more efficient renewable energy solutions which hold promise for sustainable future by reducing dependence on fossil fuels and mitigating carbon emissions.
Keywords: CdS; CdTe; chalcopyrite; photovoltaic performance; SCAPS-1D; EFFICIENCY; BULK; Physics